Daur Kha? an-Naskh f? Tanmiah Maharah al-Kit?bah bi al-Lughah al-?Arabiyah: Mur?ja?ah Manhajiyah li al-Adabiyat - Nurazizah Bancin; Anwar Sidik; Fitri Mawaddah Bako (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
?????? ?????: ???? ?????? ???? ?? ???? ????? ?????? ??????? ???????? ??????? ????????? ?? ?????? ????????? ??? ????? ??????? ??????? ??????? ?? ??? ???? ?? ????? ????? ??????? ??? ??????. ???? ??? ????? ??? ????? ??? ????? ???? ????? ?? ????? ?????? ??????? ?????? ???????? ?? ???? ?????? ?????? ????????. ????? ????? ??? ???? ???????? ???????? ???????? (Systematic Literature Review - SLR) ?????? ???????? ??????? ??? ?????. ?? ??? ???????? ?? ?????? ????? ?????? ???????? ??????? ????? ???? ??? ????? ???? ????? ?????? ???????. ????? ??????? ?? ????? ???? ????? ?? ????? ??? ?? ???? ???????? ?? ???? ??????? ???????? ????????? ??? ??????. ??? ???? ????? ?????? ??? ???? ???????? ???????? ???????? ????????? ????? ????? ??? ??? ????? ?? ??????? ????????. ???? ??????? ???? ???? ????? ???? ???? ??? ????? ????? ????? ???????. ??????? ?????????: ?????? ?????? (SLR) ? ?? ?????? ????? ??????? Abstract: Naskh script is one of the easiest types of Arabic scripts to learn and the most widely used in the educational field, making it a suitable topic for study in terms of its impact on the development of students' writing skills. This research aims to analyze the role of teaching Naskh calligraphy in developing Arabic writing skills through a systematic literature review. The research adopts the Systematic Literature Review (SLR) approach by analyzing previous relevant studies. Data were collected from scientific articles, academic journals, and research reports that focused on teaching calligraphy and writing skills. The results showed that teaching calligraphy not only improves the quality of writing, but also enhances students' aesthetic and cultural aspects. Helping factors such as the presence of qualified teachers and appropriate tools, and hindering factors such as lack of time in the curriculum were also found. The study recommends integrating calligraphy more widely into the Arabic language curriculum. Keywords: Systematic Literature Review, Naskh Script, Writing Skills